1973
DOI: 10.1037/h0034578
|View full text |Cite
|
Sign up to set email alerts
|

Show versus no show: A comparison of referral calls to a suicide prevention and crisis service.

Abstract: This study involves an exploratory content analysis of taped telephone calls to a suicide prevention and crisis service. The aim of the research was to discover variables that might differentiate between referrals resulting in "show" and those resulting in "no show." Forty calls-a show and a no show for each of 20 telephone therapists-were coded. It was concluded that a scale based on six indexes would differentiate between the two groups. Motivation of the caller for getting help and the concreteness of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
0

Year Published

1974
1974
1980
1980

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 12 publications
3
20
0
Order By: Relevance
“…In another study of actual crisis calls, Knickerbocker and McGee (1973)compared levels of empathy, warmth, and genuineness offered by lay volunteers and professionals. A series of studies has attempted to differentiate between crisis telephone interactions leading to successful and unsuccessful referrals (Slaikeu, Lester, & Tulkin, 1973;Tapp, Slaikeu, & Tulkin, 1974;Slaikeu, Tulkin, & Speer, 1975).…”
mentioning
confidence: 99%
“…In another study of actual crisis calls, Knickerbocker and McGee (1973)compared levels of empathy, warmth, and genuineness offered by lay volunteers and professionals. A series of studies has attempted to differentiate between crisis telephone interactions leading to successful and unsuccessful referrals (Slaikeu, Lester, & Tulkin, 1973;Tapp, Slaikeu, & Tulkin, 1974;Slaikeu, Tulkin, & Speer, 1975).…”
mentioning
confidence: 99%
“…Descriptions of the scales appear in Carkhuff (1969). Concretenessthe most important scale in the investigation of Slaikeu, et al (1973) --is defined by therapist's specificity of expression on a 5-point scale. At the lowest level, the therapist "leads or allows all discussion with the second person to deal only with vague and anonymous generalities."…”
Section: Methodsmentioning
confidence: 99%
“…One published study has focused on the outcome of the phone call in an attempt to relate process to who shows and who doesn't show for a scheduled appointment (Slaikeu, Lester, & Tulkin, 1973). These authors examined 40 tape-recorded telephone calls to a crisis center in which a referral was made to the center for face-to-face counseling.…”
mentioning
confidence: 99%
“…Slaikeu, Lester, and Tulkin (1973) performed a content analysis of a sample of referral calls in an attempt to differentiate between shows and no shows. They found that the caller's motivation for seeking help and the concreteness of the therapist (as measured by Truax and Carkhuff's (1967) ratings) seemed to be the most significant variables in predicting show or no show.…”
Section: (Spcs)mentioning
confidence: 99%